PENGEMBANGAN PRODUK MINYAK KEMIRI MELALUI PEMBERDAYAAN MASYARAKAT DAN PEMASARAN KREATIF DI DESA SELENGEN KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Hafiz, Lalu Muhamad Fajri; Azkia, Tina Imro’atun; Indriani, Nurul; Irham, Muhamad; Aprilia, Dwi Ayu; Aini, Zahratul; Yodita, Zahrawana Putri; Utami, Nadia Fitri; Aini, Niza Husnul; Apriani , Nurul Aulia; Suartika, I Made (Universitas Mataram, 2023)
Kemiri (Aleurites Moluccana) is a plantation commodity that has the potential to be well developed. This is strongly influenced by the candlenut market which is increasingly open due to the increasing demand for candlenut consumption, both domestically and abroad. The candlenut plant has many benefits, such as being used by people to grow hair, heal skin wounds, diarrhea, asthma and increase analgesic effects. However, the part of the plant that has high economic value is the candlenut seed. The method of implementing activities used to improve the quality of community products in hazelnut oil production uses three methods, namely processing, manufacture or design of packaging and packaging, and marketing. The results of the implementation of community empowerment practical work courses that have been carried out by KKN students in Selengan village try to participate in helping develop candlenut oil products to improve the quality of community products as a source of income in Selengen village.